Status and Decline of Amphibians of India - Das, Indraneil; Dutta, Sushil K. (Natural History Publications (Borneo) Sdn. Bhd, 2014)
The Republic of India (Fig. 1), with a total land area of 3,387,539 km2 , of which as much as 61% is arable, is home to the world’s second largest human population, after the People’s Republic of China. It is a country of exceptional biotic diversity and is listed among one of the top ten countries for biodiversity (Myers 1988, 1990). It also houses two major centres of biotic diversification (or ‘hotspots’), which are known areas of amphibian diversification: the Western Ghats (Biju et al. 2008) and northeastern India, which lies within the Eastern Himalaya (Chanda 1994; Kamei et al. 2012). In terms of its amphibian fauna India is the 11th most diverse country, after Brazil, Colombia, Ecuador, Peru, México, Indonesia, China, Venezuela, United States, and Papua New Guinea (IUCN 2009; see also Stuart et al. 2004). This diversity is attributed to the variety of ecological conditions and a complex geological history. India touches the Himalayan range and extends south to cover the entire Indian peninsula. Its political boundaries include the islands of the Bay of Bengal (Andaman and Nicobar Archipelago) and of the Arabian Sea (Lakshadweep Archipelago).